2020
DOI: 10.1287/isre.2019.0901
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Physicians’ Online-Offline Behavior Dynamics: An Empirical Study

Abstract: Online healthcare platforms allow physicians and patients to communicate in a timely manner. Yet little is known about how physicians’ online and offline activities affect each other and, consequently, the healthcare system. We collected data from both online and offline channels to study physicians’ online-offline behavior dynamics. We find that physicians’ online activities can lead to a higher service quantity in offline channels, whereas offline activities may reduce physicians’ online services be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 77 publications
0
43
0
Order By: Relevance
“…One related work that our study extends from is that of Wang et al. (2020), which explored the online–offline interaction of providers’ activities. In particular, the authors indicated that providers’ online healthcare services influence their offline demand, which in turn negatively affects their online service.…”
Section: Related Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…One related work that our study extends from is that of Wang et al. (2020), which explored the online–offline interaction of providers’ activities. In particular, the authors indicated that providers’ online healthcare services influence their offline demand, which in turn negatively affects their online service.…”
Section: Related Literaturementioning
confidence: 99%
“…For example, the offline healthcare activities of providers correlate with the number of their online consultations (Wang et al. 2020). In addition, the quality of social interactions between providers and patients online can influence the providers’ online demand (Chang et al.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing and delivering web-based services is a major trend in the digital transformation of health services [1]. Currently, increasingly more users obtain health information, consult a physician, purchase drugs, or self-manage wellness from smartphones.…”
Section: Introductionmentioning
confidence: 99%